Electrical Resistivity Tomography and Ground Penetrating Radar Measurements for Permafrost Detection on Strandartindur, Seyðisfjörður - East Iceland - Alexandra Von Der Esch 2000- (2023)
Electrical resistivity tomography (ERT) and ground penetrating radar (GPR) measurements were performed to investigate permafrost’s potential presence and distribution on the slopes of Strandartindur, a mountain above Seydisfjordur in East Iceland. This is important as permafrost is retreating in many regions of the Northern Hemisphere due to climate change, causing steep slopes to become more unstable. In Seydisfjordur, several landslide cycles have occurred in the last century, originating from the lower parts (< 500 m a.s.l.) of Strandartindur. Their triggering mechanism is being intensively studied, and the current evolution of the slope is monitored. In addition to these landslides, slow movements are observed in the upper part (> 500 - 1010 m a.s.l.) of these slopes. In these upper areas, it is unknown if permafrost is present or what causes it to creep downward. To further investigate the cause of this behavior, it is essential to know and map the distribution and condition of possible permafrost layers. Therefore, ERT and GPR measurements were conducted at four sites on the slopes of Strandartindur. Combining the two methods allows us to get a clearer picture of the subsurface and understand it better since ERT primarily addresses the electrical resistivity of the subsurface, which is strongly dependent on other factors such as porosity, water content, and temperature. GPR can help map the presence of different interfaces below the surface, determined by their different electrical properties, such as relative electrical permittivity and conductivity as well as magnetic permeability. With these measurements, we aim to answer the questions of whether permafrost is present in the selected area, what the distribution of permafrost is, whether laboratory resistivity measurement on field samples can help with interpreting the field results and deliver a calibration value, and whether these methods are appropriate for this area. Results show no clear evidence of permafrost at the investigated sites. ...